The perceived impact of social media access on rural communities in al-Ahsa Region, Saudi Arabia - Alsubaie, Abdulrhman Qasei; Novel Lyndon, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Increasing penetration of smartphones in Saudi Arabia has increased access to social media. Smartphone ownership in Saudi Arabia is 87.34% and it is projected to further increase to 97.1% by 2025. This shows that smartphone penetration in the country is double the international average. The most notable use of the internet is for social interaction and this has enhanced the popularity of social media. Social media has greatly impacted the Saudi Arabian society that is largely defined by Islamic culture. Social media a force of change and it has transformed how people interact with friends. In this qualitative study, the data was collected through a survey method and an interview instrument is the research instrument employed. The purpose of this study is to evaluate the perceived impact of social media on the rural communities in Al-Ahsa, Saudi Arabia. The study used a sample of 17 students from King Faisal University and the study found that social media access enhances social interaction, attainment of freedom, and exchange of political ideologies. Also, social media access undermines personal privacy and dilutes a rich Islamic culture. The study also established that smartphone ownership is rapidly increasing in rural areas. Results of this study found the use of social media in rural areas is simultaneously beneficial and harmful. The findings will help leaders to develop policies that enhance the benefits of social media in rural areas but protect consumers from its harmful effects.